Baseline MAPK signaling activity confers intrinsic radioresistance to KRAS-mutant colorectal carcinoma cells by rapid upregulation of heterogeneous nuclear ribonucleoprotein K (hnRNP K). (28th January 2017) - Eder, Stefan; Arndt, Annette; Lamkowski, Andreas; Daskalaki, Wassiliki; Rump, Alexis; Priller, Markus; Genze, Felicitas; Wardelmann, Eva; Port, Matthias; Steinestel, Konrad
Abstract: Heterogeneous nuclear ribonucleoprotein K (hnRNP K) is overexpressed in malignant tumors and involved in DNA damage response upon ionizing radiation (IR). Here, we investigate its role in radioresistance of colorectal carcinoma (CRC) and evaluate a pharmacological approach to enhance CRC radiosensitivity via downregulation of hnRNP K. We show that hnRNP K is overexpressed in CRC tissue specimens and upregulated in response to IR in vitro, which occurs faster in KRAS -mutant CRC cells. HnRNP K knockdown impairs cell survival, cell cycle progression and KRAS -dependent radioresistance and increases apoptosis. Using the chicken chorioallantoic membrane assay, a decrease in xenograft tumor growth and radioresistance upon hnRNP K depletion could be verified in vivo, and comparable effects were achieved by suppression of hnRNP K expression using the MEK inhibitor MEK162 (Binimetinib). In summary, KRAS -mutant CRC shows intrinsic radioresistance along with rapid upregulation of hnRNP K in response to IR that can effectively be targeted by MEK inhibition. Our results point towards a possible use of MAPK pathway inhibitors to decrease radioresistance of KRAS -mutant CRC via downregulation of hnRNP K. Highlights: hnRNP K is overexpressed in colorectal carcinoma. KRAS -mutant CRC cells show intrinsic radioresistance and rapid upregulation of hnRNP K in response to IR. hnRNP K knockdown impairs cell survival and proliferation and increases apoptosis upon IR. MEK inhibition suppresses hnRNP K expression. MEK inhibition may confer radiosensitivity to primary radioresistant CRC cells.